(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
In the mobile and digital age, technological advancements have provided numerous benefits in terms of information dissemination, education, remote work, and leisure activities. However, these advancements also bring the risk of data breaches and cyber threats at both individual and organizational levels. The ever-evolving nature of cyber threats highlights the importance of considering human factors in cybersecurity. This article provides an overview of the topic’s significance and explores the common risks and impacts in the cybersecurity field. It further emphasizes the role of human factors in security and delves into behavioral approaches. The article concludes by stating the intention to conduct research on behavioral science theories to better understand the influence of human factors in cybersecurity.